La realidad de la Guerra de la Independencia poetizada por Pedro Antonio de Alarcón - Enrique Rubio Cremades (Cuadernos de Ilustración y Romanticismo)
Alarcón reflects the literary tradition born of the War of Independence in Spain. Their Historietas nacionales narrate diverse historical episodes in which the patriotism of the Spaniards before the French invasion is shown. Alarcón shows the ancestral ethical values ​​that combine the Spanish with the religion, with the heroism, with the tradition, with the family. On the contrary, the image of the Frenchman is always represented by a denigrating prism, a barbarian one.